2018
DOI: 10.1136/bcr-2018-225003
|View full text |Cite
|
Sign up to set email alerts
|

Patient with Lynch syndrome with subsequent development of small bowel adenocarcinoma

Abstract: Small bowel adenocarcinoma (SBA) is a rare cancer in the general population, but the incidence increases in patients with Lynch syndrome. The present case describes a 57-year-old white woman with a history of colon cancer status posthemicolectomy and diagnosis of Lynch syndrome. Twenty years after her operation, the patient presented with vague abdominal discomfort and constipation, and underwent an exploratory laparotomy which revealed a stage 3A SBA. Genetic testing of the specimen provided evidence of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A high percentage of patients with small bowel cancer were diagnosed at advanced stages due to non-specific abdominal symptoms such as dull or cramping pain, distention, and obstruction [ 16 , 18 ]. Jun et al reported that the frequency of pT4 small bowel cancer was 59% for sporadic cases and 50% for Lynch syndrome [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high percentage of patients with small bowel cancer were diagnosed at advanced stages due to non-specific abdominal symptoms such as dull or cramping pain, distention, and obstruction [ 16 , 18 ]. Jun et al reported that the frequency of pT4 small bowel cancer was 59% for sporadic cases and 50% for Lynch syndrome [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Careful observation during ovarian tumor surgery allowed us to identify the ileum cancer that would have been difficult to find preoperatively in the patient. As clinical symptoms are frequently vague and non-specific, patients with ileum cancers are often diagnosed at advanced stages [10]. Furthermore, there are currently no effective methods to detect early-stage small bowel cancer in asymptomatic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ampullary duodenal carcinomas are exceedingly rare [ 2 ]. Their incidence increases in cancer-predisposing syndromes like familiar adenomatous polyposis, and MUTYH-, NTHL1-, and PPAP-associated polyposis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%